Interview with Guillermo Rendueles Olmedo, psychiatrist - Terrón Bañuelos, Aida (Historia y Memoria de la Educación, 2021)
In the course of compiling the professional biography of the psychiatrist Guillermo Rendueles, this document also charts a course through the closing decades of the twentieth century and the opening ones of the present century. It explores, as the interview unfolds, such issues as the developments in university education, the country’s political conflicts, the attempts to establish a new training system for Resident Doctors, the movement for the reform of psychiatric hospitals and the general trend in Mental Healthcare in a democratic Spain